Analisis sistem pengendalian internal pemerintah atas pengelolaan barang milik daerah pada Badan Perencanaan Penelitian dan Pengembangan Daerah Kabupaten Halmahera Barat - Lessa, Yulia; Rundengan, Fanda D. P.; Afandi, Dhullo (Yayasan Widyantara Nawasena Raharja, 2025)
This study aims to determine the internal control system over the management of regional property at the Regional Research and Development Planning Agency West Halmahera Regency with SPIP Number 60 of 2008. Type of research type of research used is qualitative with a descriptive approach. Research results regarding the Government Internal Control System for the Management of Regional Property Regional Property Management at the Regional Research and Development Planning Agency of West Halmahera Regency West Halmahera shows the elements of the control environment, risk assessment, information and communication, and monitoring have been carried out in accordance with PP Number 60 of 2008, while the element of control activities is not yet appropriate. This is This is because physical control over assets regarding security has not been well implemented.